Medical Students' Perceptions of The Role of Podcasts and Youtube in Enhancing Medical Knowledge and Their Review From an Islamic Perspective - Budiman, Diaz Viera; Komalasari, Rita; Maulidya Sari, Siti (Jurnal Health Sains, 2025)
This study explores the perceptions of medical students regarding the role of podcasts and YouTube in enhancing their understanding of medical knowledge, while also examining the factors influencing their usage and reviewing these media from an Islamic perspective. Using a descriptive qualitative approach, data were collected through in-depth interviews with third-year medical students at YARSI University who actively utilize these platforms as self-directed learning tools. The findings reveal that students perceive podcasts and YouTube as effective, flexible, and engaging resources for visualizing complex medical concepts, revising course material, and supporting individual learning preferences. Internal factors such as motivation, digital literacy, and learning styles, as well as external factors like internet access, content quality, and institutional support, significantly affect usage. From an Islamic perspective, the majority of students believe that the use of digital media for learning aligns with Islamic values, provided it is used with sincere intentions and does not interfere with religious obligations. This study highlights the growing relevance of digital media in modern medical education and supports its integration into curriculum design with consideration of ethical and religious values.